Gerador a relutância variável em conexão com a rede elétrica para injeção de potência ativa - Viajante, Ghunter Paulo (2013)
This work shows a contribution to the study of the Switched Reluctance Machine driven as a generator to connecting in the grid to inject active power. The main objective is show the Switched Reluctance Generator behavior under various operating conditions, as well as the development of an electronic converter to connect it to the low voltage grid. Thus, it presents a mathematical model for the Switching Reluctance Generator which includes the magnetic circuit saturation and a computational model for analyzing steady state and transient. Also it is presented a strategy of generated voltage control by the magnetization angle variation acting only in the top switch of the Asymmetrical Half Bridge converter. An intermediate stage was added in the switching control strategy to reduce the energy amount provided by the excitation source and get better utilization of electromechanical conversion. A detailed description of the control system equations of the DC-AC stage, PLL algorithm and design of injected current compensator are presented and discussed. Finally, it was constructed in laboratory a experimental platform for verification of the theoretical and simulation.